Study guides

Q: Square root 2a

Write your answer...

Submit

Related questions

-b + or - the square root of b squared - 4ac over/divided by 2a

(−b±√b2−4ac)÷2a the square root of b2−4ac entirely.

Say the monomial is 4a squared. To find the square root to must do each part seperately. So square root of 4 is 2 and the square root of a-squared is |a| because we do not know the sign of a. The answer is 2|a|. If there is anything that cannot be "square rooted" then it would stay under a square root sign and just multiply by 2a as well. The principal root of a number is only its positive root (you can understand that you are looking for the principal root from the sign in front of the radical, which is a positive one)

One side of the square, RA, is 2a cm. So the area of the square is (2a)2 = 4a2 cm2

√20a2b = √4a2 * √5b = 2a√5b the answer is 2a times radical 5b.

The quadratic formula is x=-b (+or-) square root of b2-4ac all over 2a

In the quadratic formula, the discriminant is b2-4ac. If the discriminant is positive, the equation has two real solutions. If it equals zero, the equation has one real solution. If the discriminant is negative, it has two imaginary solutions. This is because you find the square root of the discriminant and add or subtract it from -b and divide the sum or difference by 2a. If the square root is of a positive number, then you get two different solutions, one from adding the discriminant to -b and one from subtracting the discriminant from -b. If the square root is of zero, then it equals zero, and the solution is -b/2a. If the square root is of a negative number, then you have two imaginary solutions because you can't take the square root of a negative number and get a real number. One solution is from subtracting the discriminant from -b and dividing by 2a, and the other is from adding it to -b and dividing by 2a. The parabola on the left has a positive discriminant. The parabola in the middle has a discriminant of zero. The parabola on the right has a negative discriminant.

33

x equals negative b plus or minus the square root of b squared minus 4bc over 2a

X2+5x-6. a=1, b=5, and c=-6 The formula is: -b plus or minus the square root of b squared minus 4ac all over 2a. -b+square root of b2-4ac ---- 2a -5 plus or minus the square root of 5 squared minus 4(1)(-6) -5 plus or minus the square root of 25-4(-6) -5 plus or minus the square root of 25+24 -5 plus or minus the square root of 49 -5 plus or minus 7 Here is where you split into two different answers: Number 1: -5 plus 7= 2 Number 2: -5 minus 7= -12 Your answer is X=2, -12

Depends what type of equation you want. My favourite is the quadratic equation. (-B plus or minus the square root of B - 4AC) Divided by 2A

x = (-b plus_minus root(b2 - 4ac)) / 2aWhere plus_minus is the "plus or minus" sign, and "root" stands for the square root.

The quadric equation is: negative b plus or minus the square root of b squared minus 4ac all over(divided by) 2a

If you are using square roots, the simplest way of solving: ax2 + bx + c = 0 is x = [-b Â± sqrt(b2-4ac)]/(2a)

The first step is to write the quadratic in the form ax^2 + bx + c = 0 where x is the variable and a, b and c are constants. Then the two solutions are [- b - sqrt(b^2 - 4ac)]/(2a) and [- b + sqrt(b^2 - 4ac)]/(2a)

4a2+ 25 does not factor over the real number field. In the complex numbers , it factors as (2a +5i)(2a - 5i). This is because i2 = -1, so 4a2 + 25 = 4a2 - (- 25) = 4a2 - 25(-1) = 4a2 - 25i2

midpoint: (x1+x2/2 , y1+y2/2) quadratic: -b plus or minus square root b squared minus 4ac divided by 2a

The quadratic formula originated from the concept of completing the square. let's take ax2 + bx + c = 0. To complete the square, solve for x. Subtract c. ax2 + bx = -c. Then divide by a [notice- if there is no a value, then a=1]. x2 + bx/a = -c/a. Add (b/2a)2 to both sides. x2 + bx/a + b2/4a2 = -c/a + b2/4a2 Factor/Reformat. (x + b/2a)2 = (b2-4ac) / 4a2 (x + b/2a)2 = [(b2-4ac) / 2a]2 Square-root both sides. x + b/2a = ± √(b2-4ac) / 2a Subtract b/2a. x = -b/2a ± √(b2-4ac) / 2a Combine terms. x = [-b ± √(b2-4ac)] / 2a

The quadratic formula originated from the concept of completing the square. let's take ax2 + bx + c = 0. To complete the square, solve for x. Subtract c. ax2 + bx = -c. Then divide by a [notice- if there is no a value, then a=1]. x2 + bx/a = -c/a. Add (b/2a)2 to both sides. x2 + bx/a + b2/4a2 = -c/a + b2/4a2 Factor/Reformat. (x + b/2a)2 = (b2-4ac) / 4a2 (x + b/2a)2 = [(b2-4ac) / 2a]2 Square-root both sides. x + b/2a = ± √(b2-4ac) / 2a Subtract b/2a. x = -b/2a ± √(b2-4ac) / 2a Combine terms. x = [-b ± √(b2-4ac)] / 2a

The side is square root of 40.5. ( approximately 6.363961...) The diagonal is 6.363961...times the square root of 2, because of the Pythagorean formula of a^2+b^2=c^2 a^2+a^2=c^2 square has identical sides. 2a^2 =c^2 a * sqr 2=c square root both sides of the equation. a is the side of the square. So, 6.363961... times sqr 2= 9

6x² - 17x +12 = Quadratic equation X = (-b +/- (square root of b² - 4ac)) divided by 2a X = (--17 +/- square root of 289-288)) divided by 12 X = 1.5 or 1.333333 recurring

This is a quadratic equation in the form of x2-2x-1 = 0 which will have two solutions and can be solved using the quadratic equation formula: x = -b/2a + and - the square root of (b2-4ac)/2a Whereas in this equation a = 1, b = -2 and c = -1 Solutions: x = 1-the square root of 2 or x = 1+the square root of 2 Remember that (- -2) = 2, (-2)2 = 4 and (-4*1*-1) = 4

In the quadratic formula, you have -b +- square root of ( b^2 - 4ac) all over 2a. There are three cases:No values:If the discriminant is negative, the square root of b^2 -4ac has no values, because we cannot take the square root of a negative number.One value:If it is zero, than the square root is also zero. This means that there is one solution because +- 0 is always just 0. (-b+-0)/2a only has one value.2 values:if the discriminant is positive then it has a square root. BUT, there is a difference between here and the last step. (-b +- discriminant )/ 2a has 2 values: one for the positive and one for the negative.* * * * *Minor amendment:-b +- square root of ( b^2 - 4ac) all over 2a is the quadratic formula.The discriminant is simply b2 - 4acIf b2 - 4ac > 0 then there are two distinct real roots to the quadratic;If b2 - 4ac = 0 then there is one real roots to the quadratic (or two identical roots);If b2 - 4ac < 0 then there are no real roots to the quadratic.The values of the roots are exactly as described in the earlier answer.

The general quadratic equation is ax2 + bx + c = 0 The two solutions are: x = [ (negative b) plus or minus the square root of (b2 - 4ac) ] all divided by (2a).

How you solve an equation that doesn't factor is to plug a quadratic equation's format; ax2+bx+c into the quadratic formula which is x=-b+square root to (b2-4ac)/2a.